Exfoliation and characterization of V2Se9 atomic crystals - Kim, Bum Jun; Jeong, Byung Joo; Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Nasir, Tuqeer; Lee, Sang Hoon; Kim, Kwan Woo; Lim, Hyung Kyu; Choi, Ik Jun; Moon, Ji Yun; Yu, Hak Ki; et al. (Nanomaterials, 2018)
Mass production of one-dimensional, V2Se9 crystals, was successfully synthesized using the solid-state reaction of vanadium and selenium. Through the mechanical exfoliation method, the bulk V2Se9 crystal was easily separated to nanoribbon structure and we have confirmed that as-grown V2Se9 crystals consist of innumerable single V2Se9 chains linked by van der Waals interaction. The exfoliated V2Se9 flakes can be controlled thickness by the repeated-peeling method. In addition, atomic thick nanoribbon structure of V2Se9 was also obtained on a 300 nm SiO2/Si substrate. Scanning Kelvin probe microscopy analysis was used to explore the variation of work function depending on the thickness of V2Se9 flakes. We believe that these observations will be of great help in selecting suitable metal contacts for V2Se9 and that a V2Se9 crystal is expected to have an important role in future nano-electronic devices.
Keywords: Atomic crystal; Mechanical exfoliation; Scanning kelvin probe microscopy; V2Se9